2012
DOI: 10.1097/pec.0b013e318271733e
|View full text |Cite
|
Sign up to set email alerts
|

A New After-Hours Clinic Model Provides Cost-Saving, Faster Care Compared With a Pediatric Emergency Department

Abstract: Our AHC model showed a significant reduction in length of stay and charges in compared demographically and clinically matched PED patients. This may be an effective model to help address emergency department overcrowding and promote patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…9 Recently, a national parent survey demonstrated that among enhanced access services including same-day sick visits, phone advice outside office hours, and e-mail advice, only extended primary care office hours (after 5 pm on 5 or more nights a week) was associated with decreased ED use. 5 Sterner et al 10 recently reported a cost saving of an AH pediatric clinic versus a pediatric ED. In their model, patients were triaged by a phone nurse and referred to the ED or AH clinic by appointment only.…”
Section: Discussionmentioning
confidence: 99%
“…9 Recently, a national parent survey demonstrated that among enhanced access services including same-day sick visits, phone advice outside office hours, and e-mail advice, only extended primary care office hours (after 5 pm on 5 or more nights a week) was associated with decreased ED use. 5 Sterner et al 10 recently reported a cost saving of an AH pediatric clinic versus a pediatric ED. In their model, patients were triaged by a phone nurse and referred to the ED or AH clinic by appointment only.…”
Section: Discussionmentioning
confidence: 99%
“…We identified four common themes across these interventions and grouped them under these following themes: (1) improving timely access to primary care, (2) integrating hospital and GP care, (3) providing financial support and (4) implementing new clinics/ services (online supplemental appendix table 6). Some examples of the 'outside ED' interventions or strategies were: increasing after-hours primary care, 37 free access to primary care for the uninsured, 38 adjacent or co-located primary care clinic for lower acuity patients, 39 introduction of a patient-centred medical home that addresses primary care needs of patients, 40 implementation of GP cooperatives (out-of-hours primary healthcare in one centrally located practice), 41 urgent care collaborations between the GP and ED, 42 GP-led walk-in centres, 43 PCP blended fee for service, 44 hospital-integrated general practice for emergency care services, 45 integrated emergency posts where care is provided by both ED and GPs, 46 rural health clinics 47 and advanced access primary care with timely access. 48 Involvement of primary healthcare providers The type of PHCP involved in the interventions or strategies involving PHCPs were as follows: family physician (n=85, 31.7%), NP (n=69, 25.7%) or nurse given increased authority (n=43, 16%).…”
Section: Interventions and Strategies Involving Phcpsmentioning
confidence: 99%
“…Younger age was found to be a risk factor in driving the nonurgent ED use in this review 9 . From a cost-benefit analysis, median costs related to treatment for common diagnoses in an ED can be 4 to 5 times higher in comparison with similar care provided for the same conditions in a pediatric clinic 10,11 …”
mentioning
confidence: 99%